SPAWNING PERFORMANCE AND EMBRYONIC DEVELOPMENT OF RED EMPEROR SNAPER (Lutjanus sebae) - Philip Teguh Imanto; Regina Melianawati; Made Suastika (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Snapper is one of economical marine ............